Typologies of the North: Mediating ‘Northerness’ in Jazz in Scandinavia - Gagatsis, Alexander (Nordlit, 2020)
In this article I examine some of the ways that accounts of jazz in Scandinavia have been focusing on a taxonomy of features most often associated with folk music and the remote geography of the north. I focus on specific musicians and collaborations from Norway, Denmark, and Sweden in the second half of the twentieth century, to explore issues of folklorism and landscape, questioning the degree to which perceptions of ‘northerness’ in jazz have been paired with notions of nationalism. I conclude by looking at the extent to which elements of neo-traditionalism were at play in diverse forms of cultural practice in the late twentieth century, examining the inward-looking folklorism often associated with ‘the Nordic tone’.